PENGARUH TERAPI AKUPUNKTUR TERHADAP INTENSITAS NYERI PADA KLIEN DENGAN NYERI KEPALA PRIMER - I Putu Pande Eka Krisna Yoga; Ni Luh Putu Eva Yanti; I Wayan Suardana (Coping: Community of Publishing in Nursing, 2016)
Primary headache is a headache which is not yet clearly an anatomical abnormalities, structural abnormalities or others precipitation. The factor that can trigger primary headaches such as stress, physical exercise, diet, alcohol, and hormones. Primary headache can be treated with acupuncture therapy. Acupuncture therapy is a therapeutic insertion of needles in the head and acupoints in the body. The aim of this study determines the therapeutic effect of acupuncture pain intensity on clients with primary headaches. This study is a pre-experimental studies (one-group pre-test post-test design). The technical sampling use incidental sampling and there are chosen 35 respondents. Data collected by using a sheet instrument to get demographic data and pain scale. The research find before acupuncture therapy, 28 respondents with moderate pain, 6 respondents with severe pain and 1 respondents with mild pain. The pain scale after a there are decreasing pain scale. The 16 respondents with moderate pain and 19 respondents with mild pain. The results obtained by Wilcoxon test, there are therapeutic effect of acupuncture on pain intensity in patients with primary headache. Based on these results suggested nurse to use acupuncture therapy besides pharmacological therapy.